GP276 Audit of newborn screening cork university hospital2011–2019 – impact of gestational age on sweat testing. (June 2019) - Gallagher, Aoife; Hooley, Katherine; Costello, Sean; Felsenstein, Susanna; Mullane, David; NíChróinín, Muireann
Abstract : Background: A previous national audit looking at sweat testing in all age groups in 2011 found Cork University Hospital (CUH) had a high number of tests with quantity not sufficient (QNS) result. Since then there has been new equipment and staff training. International laboratory audit criteria examine failure rates for under 6 months which has recently been <1% in CUH (acceptable<5%). However higher failure rates (0–40%) for sweat testing have been noted internationally in newborn screening programmes, a more difficult cohort to successfully sweat test. Aims: Sweat tests performed in CUH from 2011–2018 as part of newborn screening in relation to number of patients with positive (>60), negative (<30), equivocal and QNS results were reviewed. The gestational age at birth and at time of testing and birth weight were examined as potential variables. Methods: Ethical approval obtained: Newborn screening records for all patients from July 2011 to December 2018 reviewed. Sweat testing data obtained from laboratory. Data analysed using SPSS and Chi-Square test. Results: 102 infants referred to Cork for sweat testing as part of newborn screening. Patients diagnosed by meconium ileus (n=7), had sweat testing elsewhere (n=1) or had antenatal diagnosis (n=2) were not included (N= 10). On initial testing 30 patients had a QNS result (32.6%). 7 had same day repeat testing which was sufficient, the remaining having sweat testing at a later date. Ultimately there were 23 with positive tests, 67 with negative tests, 2 equivocal tests. Gestational age and birth weight of the 30 patients with initial QNS result were compared to the 62 with successful testing. Infants were divided into two groups based on gestation, 38 weeks and below and 39 weeks and above. Results were dichotomised into sufficient and insufficient (QNS) results. The Chi square test indicated that there is a statistically significant association between gestational age and sufficient or insufficient result. (p=0.004) Discussion: It would be helpful to compare our data to the same cohort in other centres and national rate to see if this is an acceptable QNS rate and obtain further data regarding gestational age. Collection techniques and laboratory analysis have already been optimised with current equipment and staff. Consideration could be given to delay offering sweat test by one to two weeks to those born at 37 and 38 weeks gestation in infants who only have 1 mutation. This may reduce need for time consuming and stressful repeat testing.